Interleukin 8 as a vaso-occlusive marker in Brazilian patients with sickle cell disease - Gonçalves, Marilda de Souza (2001)
Fundação Oswaldo Cruz. Centro de Pesquisas Gonçalo Moniz. Salvador, BA, Brasil